NMR diffusion diffraction and diffusion interference from cells - Kuchel, Philip W.; Pages, Guilhem (Diffusion Fundamentals, 2007)
Pulsed field gradient spin-echo (PGSE) NMR spectroscopy is the definitive means for measuring translational motion of molecules in free solution and in heterogeneous systems. A unique ‘twist’ on the method is that in some systems in which diffusion is restricted the PGSE experiment yields information on the geometrical properties of the confining boundaries. When applied to red blood cells (RBCs) in suspensions, using intense magnetic field gradients (around 10 T m-1), the graph of normalized NMR-signal intensity versus the magnitude of the field gradients has the form of the diffraction and interference patterns that are seen in physical optics. We review here the nature of these so called q-space plots and discuss a data-processing method that adds objectivity to estimates of the mean RBC diameter. Convection potentially interferes with the veracity of these measurements so an experiment is reported in which a cell-free sample was deliberately made to flow. The very simple analysis of flow diffraction yielded estimates of flow that were in remarkable agreement with gravimetric measurements. Finally, in a theoretical study using a model of uniformly arrayed octagonal prisms that were ‘morphed’ in a systematic way, the dependence of the form of q-space plots on prism shape and packing density was obtained. This showed that elaborately shaped q-space plots can be obtained from simple periodic arrays of ‘cells’. The uniqueness or otherwise of shapes of q-space plots, and the prospect of generally solving the inverse problem whereby q-space analysis yields detailed information on packing arrangements is poised for further detailed investigations.